Human-Directed Optical Music Recognition - Chen, Liang; Raphael, Christopher (Electronic Imaging, 2016)
We propose a human-in-the-loop scheme for optical music recognition. Starting from the results of our recognition engine, we pose the problem as one of constrained optimization, in which the human can specify various pixel labels, while our recognition engine seeks an optimal explanation subject to the humansupplied constraints. In this way we enable an interactive approach with a uniform communication channel from human to machine where both iterate their roles until the desired end is achieved. Pixel constraints may be added to various stages, including staff finding, system identification, and measure recognition. Results on a test show significant speed up when compared to purely human-driven correction.